The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1039/d1fo01125a
|View full text |Cite
|
Sign up to set email alerts
|

Fruits and their impact on the gut microbiota, gut motility and constipation

Abstract: Fruits are the seed-bearing product of plants and have considerable nutritional importance in the human diet. The consumption of fruits is among the dietary strategies recommended for constipation due to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 119 publications
(140 reference statements)
1
29
0
1
Order By: Relevance
“…Both dietary fiber and plant polyphenols associated with dietary fiber have been shown to modulate the composition and metabolic activity of the intestinal microbiota [42][43][44]. Similarly, prebiotics have been shown to increase the abundance of intestinal bifidobacteria and lactobacilli, organisms considered beneficial for human health and often used as probiotics [45].…”
Section: Discussionmentioning
confidence: 99%
“…Both dietary fiber and plant polyphenols associated with dietary fiber have been shown to modulate the composition and metabolic activity of the intestinal microbiota [42][43][44]. Similarly, prebiotics have been shown to increase the abundance of intestinal bifidobacteria and lactobacilli, organisms considered beneficial for human health and often used as probiotics [45].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, carboxymethylcellulose, a widely used emulsifier, has been shown to act as a laxative54 and was recently linked to reduced gut microbiota diversity in humans 55. Another example is sorbitol, a sugar alcohol highly abundant in prunes, which can retain water molecules by osmosis, similar to some types of fibre that increase water content in the gut lumen and may lead to softer stools 56 57. In addition, consumption of turmeric, a spice increasing the bile secretion, has been associated with a significantly longer transit time in gnotobiotic mice 58…”
Section: Transit Time Throughout the Gitmentioning
confidence: 99%
“…In 2021, a recent systematic review of trials showed that various fruits, such as prunes, raisins, and apple fiber, could increase fecal weight. The present study suggests that apple, kiwifruit, fig paste, and orange may reduce gut transit time but prunes do not ( 17 ).…”
Section: Introductionmentioning
confidence: 74%
“…A recent systematic review published in 2021 has suggested that there is some evidence for the effects of fruits on gut motility due to gut physiology and microbiota and are helpful in constipation symptom alleviation. However, it is hard to know the effects of fruits and the specific mechanisms behind their potential ( 17 ).…”
Section: Discussionmentioning
confidence: 99%